Teacher’s Competencies in Designing Lessons to Improve Students’ Learning Outcomes - Indah Faridah; Wahidin Wahidin; Ria Yulia Gloria (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Teachers’ competencies initiated this research in learning preparation, including planning and implementing the learning process, understanding materials, evaluating learning outcomes, and actualizing students’ potential to develop. Therefore, teachers’ competencies are necessary to design learning and improve learning outcomes. This study aimed to determine teachers’ competencies to design learning and enhance learning outcomes. This research was descriptive qualitative research. It investigated conducted at SMAN 1 Ciwaringin in April 2019 (the second semester of the 2018-2019 academic year). The research subject was teacher IW. The data were collected using observation, documentation, and test techniques. The respondent’s competencies in designing learning were seen from four aspects: syllabus, learning process, and evaluation. This research revealed that the teachers’ ability to design learning tools, processes, and ways for class XI students at SMAN 1 Ciwaringin was good. Moreover, the students’ biology learning outcomes increased significantly, as indicated by the pretest and posttest scores conducted before and after the learning. This study also discovered that the teacher IWs’ ability to design learning improved students’ learning outcomes.